2003
DOI: 10.1164/rccm.2112062
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Endotoxin Predicts Symptoms in Non–Mouse-sensitized Technicians and Research Scientists Exposed to Laboratory Mice

Abstract: Research scientists, laboratory technicians, and animal handlers who work with animals frequently report respiratory and skin symptoms from exposure to laboratory animals (LA). However, on the basis of prick skin tests or RASTs, only half are sensitized to LA. We hypothesized that aerosolized endotoxin from mouse work is responsible for symptoms in nonsensitized workers. We performed a cross-sectional study of 269/310 (87%) workers at a research institution. Subjects completed a questionnaire and underwent pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
2
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 43 publications
2
48
2
2
Order By: Relevance
“…We found that endotoxin was strongly positively associated with asthma at low levels of specific IgE against dog, mouse, and rat but negatively associated with asthma at high levels of IgE against mouse and rat. Likewise, in a sample of laboratory scientists and technicians, Pacheco and colleagues looked at the association of aerosolized endotoxin with symptoms related to mouse by sensitization status and concluded that endotoxin predicts respiratory symptoms related to mice in non-mouse-sensitized participants (31).…”
Section: Discussionmentioning
confidence: 99%
“…We found that endotoxin was strongly positively associated with asthma at low levels of specific IgE against dog, mouse, and rat but negatively associated with asthma at high levels of IgE against mouse and rat. Likewise, in a sample of laboratory scientists and technicians, Pacheco and colleagues looked at the association of aerosolized endotoxin with symptoms related to mouse by sensitization status and concluded that endotoxin predicts respiratory symptoms related to mice in non-mouse-sensitized participants (31).…”
Section: Discussionmentioning
confidence: 99%
“…The development of LAA is due to the presence of IgE antibodies directed against animal proteins, and incidence rates are rapidly increasing. Hair shaving increases the chance of direct exposure of the researcher to the animal proteins, and the worst possible outcome of LAA is death by anaphylactic shock (Pacheco et al, 2003, Schweitzer et al, 2003, Matsui et al, 2004, Curtin-Brosnan et al, 2010. Therefore, a hairless model on an AD-prone genetic background would be an ideal and powerful tool for basic research, such as the discovery of the genes responsible for AD, and for drug development, such as the development of new ointment for the treatment of AD.…”
Section: Details Of the Nc Modelmentioning
confidence: 99%
“…Second, exposure to these irritants alone can also predispose individuals to asthmatic symptoms [Medina-Ramón et al, 2005;Massin et al, 2006]. Third, respiratory symptoms following exposure to laboratory animals may be a consequence of exposure to endotoxins, rather than to animal allergens as such [Pacheco et al, 2003]. Despite these confounding factors, few research groups have attempted to address the problematic question of threshold levels of allergens.…”
mentioning
confidence: 99%